Green and Roasted Coffee Extracts Inhibit Interferon-β Release in LPS-Stimulated Human Macrophages - Artusa, Valentina; Ciaramelli, Carlotta; D’Aloia, Alessia; Facchini, Fabio Alessandro; Gotri, Nicole; Bruno, Antonino; Costa, Barbara; Palmioli, Alessandro; Airoldi, Cristina; Peri, Francesco (Frontiers in Pharmacology, 2022)
The anti-inflammatory activity of coffee extracts is widely recognized and supported by experimental evidence, in both in vitro and in vivo settings, mainly murine models. Here, we investigated the immunomodulatory properties of coffee extracts from green (GCE) and medium-roasted (RCE) Coffea canephora beans in human macrophages. The immunomodulatory effect of GCE and RCE was characterized in an LPS-induced inflammation model in THP-1-derived human macrophages (TDM). Results showed decreased amounts of TNF-α, IL-6 and IL-1β and a strong dose-dependent inhibition of interferon-β (IFN-β) release. Molecular mechanism of IFN-β inhibition was further investigated by immunofluorescence confocal microscopy analysis that showed a diminished nuclear translocation of p-IRF-3, the main transcription factor responsible for IFN-β synthesis. The inhibition of IFN-β release by RCE and GCE was also confirmed by using human primary CD14+ monocytes-derived macrophages (MDM). The main component of coffee extracts, 5-O-caffeoylquinic acid (5-CQA) also inhibited IFN-β production, through a mechanism occurring downstream to TLR4. Inhibition of IFN-β release by coffee extracts parallels with the activity of their main phytochemical component, 5-CQA, thus suggesting that this compound is the main responsible for the immunomodulatory effect observed. The application of 5-CQA and coffee derived-phytoextracts to target interferonopathies and inflammation-related diseases could open new pharmacological and nutritional perspectives.